Efeito de processos de modificação térmica na composição química e na cor da madeira juvenil de tectona grandis l.f. - Gomes, Felipe da Silva (2022)
Understanding the effect of different thermal modification processes on the same material is important for decisions about industrial facilities and for choosing the use of products. The general objective of this work was to analyze the effect of closed-system and open-system thermal modification processes on juvenile teak wood. Thermally modified wood was evaluated in a closed system at 160 °C (CS160) and in an open system at 185 ºC and 210 ºC (OS185 and OS210), in addition to the Control (untreated wood). The processes were analyzed in terms of final moisture content and corrected mass loss (CML). For the chemical composition of the wood, the contents of alpha-cellulose, hemicelluloses, lignin, and extractives (total, in acetone and dichloromethane) were analyzed. The CIELab color space was used to evaluate the color of the wood, based on measurements before and after the thermal modification (paired samples). CS160 had the highest CML and caused the greatest changes in wood chemical composition compared to the Control. Even though the tested processes were different, there was correspondence between the colorimetric parameters of the CS160 and OS210 treatments. The OS185 treatment was the most similar to the Control, due to the low CML of this process (close to zero).